CYLD regulates spindle orientation by stabilizing astral microtubules and promoting dishevelled-NuMA-dynein/dynactin complex formation - Yang, Yunfan; Liu, Min; Li, Dengwen; Ran, Jie; Gao, Jinmin; Suo, Shaojun; Sun, Shao-Cong; Zhou, Jun (Proceedings of the National Academy of Sciences - PNAS, 2014)
Oriented cell division is critical for cell fate specification, tissue organization, and tissue homeostasis, and relies on proper orientation of the mitotic spindle. The molecular mechanisms underlying the regulation of spindle orientation remain largely unknown. Herein, we identify a critical role for cylindromatosis (CYLD), a deubiquitinase and regulator of microtubule dynamics, in the control of spindle orientation. CYLD is highly expressed in mitosis and promotes spindle orientation by stabilizing astral microtubules and deubiquitinating the cortical polarity protein dishevelled. The deubiquitination of dishevelled enhances its interaction with nuclear mitotic apparatus, stimulating the cortical localization of nuclear mitotic apparatus and the dynein/dynactin motor complex, a requirement for generating pulling forces on astral microtubules. These findings uncover CYLD as an important player in the orientation of the mitotic spindle and cell division and have important implications in health and disease.